Efficacy and safety of nintedanib in Japanese patients with progressive fibrosing interstitial lung diseases: Subgroup analysis of the randomised, double-blind, placebo-controlled, phase 3 INBUILD trial. (October 2021) - Inoue, Yoshikazu; Suda, Takafumi; Kitamura, Hideya; Okamoto, Masaki; Azuma, Arata; Inase, Naohiko; Kuwana, Masataka; Makino, Shigeki; Nishioka, Yasuhiko; Ogura, Takashi; Takizawa, Ayako; Ugai, Hiroyuki; et al.
Abstract: Background: The efficacy of nintedanib in progressive fibrosing interstitial lung diseases (ILDs) was demonstrated in the randomised, double-blind, placebo-controlled INBUILD trial. This subgroup analysis evaluated the efficacy and safety of nintedanib in the Japanese population. Methods: Patients with progressive fibrosing ILDs (evaluated by physicians within 24 months of screening) were randomised (1:1) to twice-daily 150-mg nintedanib or placebo; treatment continued until the last patient completed 52 weeks. The primary endpoint was the annual rate of decline in forced vital capacity (FVC) over 52 weeks. Time-to-first acute ILD exacerbation or death and time-to-death up until the last patient had completed the week 52 visit were evaluated. This subgroup analysis included 108 Japanese patients. Results: The adjusted annual rates of FVC decline (mL/year) over 52 weeks for Japanese patients were −148.31 (nintedanib) and −240.36 (placebo), adjusted difference: 92.05 (95% CI: −10.69–194.80) and for non-Japanese patients were −67.41 (nintedanib) and −177.65 (placebo), adjusted difference: 110.24 (95% CI: 64.97–155.52). No heterogeneity in treatment effect between Japanese and non-Japanese subgroups was observed (treatment-by-subgroup interaction, p = 0.75). The risks of "acute exacerbation or death" (hazard ratio, 0.30 [95% CI: 0.10–0.91]) and mortality (hazard ratio, 0.54 [95% CI: 0.14–2.11]) in Japanese patients were numerically lower for nintedanib than placebo. There were no new or unexpected safety findings. Conclusions: In Japanese patients, nintedanib slowed ILD progression, evidenced by a reduction in the annual rate of decline in FVC vs placebo. The efficacy and safety of nintedanib in Japanese patients were consistent with the overall INBUILD population. Clinicaltrials.gov: NCT02999178 (21-Dec-2016). Highlights: Chronic fibrosing interstitial lung diseases (ILDs) have significant mortality and morbidity. Nintedanib, a small molecule inhibitor of selected tyrosine kinases, is approved for ILD treatment. The efficacy of nintedanib for ILD was shown in the phase 3 randomised controlled INBUILD trial. The efficacy and safety of nintedanib in the Japanese subpopulation was similar to INBUILD overall.